Educational theory as rhythmic action: From Arendt to Agamben - Davids, N.; Waghid, Y. (South African Journal of Higher Education, 2017)
Traditionally, educational theory has been couched as modes of human action through concepts such as poiesis and praxis. Inasmuch as poiesis and praxis have significantly shaped educational theory, we argue that such modes of action – if considered as mutually exclusive – do not sufficiently explain the interrelationship between educational theory and practice. Firstly, we extend the notion of action as explained by Arendt. Next, we offer an account of Agamben’s ‘opening of rhythm’, which integrates the notions of poiesis and praxis to pave the way for an understanding of educational theory as creative will that moves human action from enacting the unexpected into ‘an increasingly free and rarified atmosphere’. Secondly, in re-examining the Aristotelian concepts of poiesis and praxis, we argue that Agamben’s ‘opening of rhythm’ extends the Arendtian notion of action to perform the unexpected, and offers an as yet unexplored lens through which to understand the nexus between educational theory and practice.